SOCIAL ISOLATION, SLEEP DISTURBANCE, AND COGNITIVE HEALTH: A LONGITUDINAL MEDIATION STUDY. (20th December 2022) - Qi, Xiang; Pei, Yaolin; Malone, Susan; Wu, Bei
Abstract: Research indicates that social isolation is associated with dementia, but the role of sleep on this association is less known. We aimed to examine the impact of social isolation on cognitive function, and how sleep disturbance mediated the association. Data came from the 2006, 2010, and 2014 waves of the Health and Retirement Study. Participants aged 50+ who completed the Psychosocial and Lifestyle Questionnaire in 2006 were included (n=5, 036). Measures include the Social Isolation Index, modified Jenkins Sleep Scale, and Telephone Interview of Cognitive Status. Cross-lagged panel models were used in the analysis. After controlling socio-demographics, lifestyle, and loneliness, social isolation predicted subsequent sleep disturbance (β=0.05; P<0.01), which in turn predicted worse cognitive functioning (β=-0.02; P<0.01). The reverse pathways from cognitive function to social isolation were also statistically supported. Public health initiatives could reduce sleep disturbance by facilitating social integration and participation in community activities, thereby protecting against cognitive decline.